Do Economic Incentives Promote Physical Activity? Evidence from the London Congestion Charge - Ryota Nakamura; Andrea Albanese; Emma Coombes; Marc Suhrcke (Global Labor Organization (GLO), 2021)
This study investigates the impact of economic incentives on travel-related physical activity, leveraging the London Congestion Charge's disincentivising of sedentary travel modes via increasing the cost of private car use within Central London. The scheme imposes charges on most types of cars entering, exiting and operating within the Central London area, while individuals living inside the charging zone are eligible for a 90% reduction in congestion charges. Geographical location information provides the full-digit postcode data necessary to precisely identify the eligibility for the discount of participants in the London Travel Demand Survey for the period 2005-2011. Using a boundary regression-discontinuity design reveals a statistically significant but small impact on active commuting (i.e. cycling and walking) around the border of the charging zone. The effect is larger for lower-income households and car owners. The findings are robust against multiple specifications and validation tests.
Keywords: D04; I12; R48; 330; economic incentive; health behaviour; London Congestion Charge; geographical information system; regression-discontinuity